Nomenclatural notes on saline vegetation of Ukraine, southern Russia and Kazakhstan - Lysenko, T.; Mucina, Ladislav; Iakushenko, D. (Universidad Complutense de Madrid, 2011)
In this syntaxonomic nomenclature note we introduce the Plantagini salsae-Artemision santonici (Artemisia santonicae-Limonietalia gmelinii, Festuco-Puccinellietea), a new name for the syntaxon carrying an illegitimate name 'Artemis ionsantonici Shelyag-Sosonko & Solomakha 1987'. This vegetation comprises Artemisia santonicum dominated salt-steppevegetation on solonetz-like soils of slightly elevated habitats of alluvial plains and of the slopes of shallow depressions inthe steppe zone of Ukraine and forest-steppe and steppe zones of Russia. We also suggest a nomenclatural adjustment(nomen inversum) for the 'Artemisio pauciflorae-Camphorosmion monspeliacae' (Artemisietalia pauciflorae, FestucoPuccinellietea).The steppe vegetation classified within this latter syntaxon occurs in southern Russia and northern Kazakhstan.